Disrupted Development in the Congo The Fragile Foundations of the African Mining Consensus - Radley, Ben (Critical Frontiers of Theory, Research, and Policy in International Development Studies, 2024)
Since the turn of the century, low-income African countries have undergone a process of mining industrialization led by transnational corporations. The process has been sustained by an African Mining Consensus uniting international financial institutions, African governments, development agencies, and various strands of the academic literature. The Consensus holds that transnational mining corporations are best placed to drive structurally transformative processes of mining-based development on the continent. State-owned enterprises and local forms of labour-intensive mining are deemed unsuitable. The former is characterized as corrupt and mismanaged, and the latter as an inefficient, subsistence activity with links to conflict financing. Through a detailed case study of gold mining in the Democratic Republic of the Congo, Disrupted Development in the Congo reveals the fragile foundations on which this consensus rests. The book documents how foreign mining corporations in the Congo have been prone to mismanagement, inefficiencies, and rent-seeking, and implicated in fuelling conflict and violence. In addition, the book details how structural impediments to the transformative effects of mining industrialization in low-income settings occur irrespective of ownership and management structures. In light of these constraints, and the levels of overseas surplus extraction and domestic marginalization associated with foreign-owned industrial mining, a shift to domestic-owned forms of mining-based development would better meet the needs of low-income African economies for rising productivity, labour absorption, and the domestic retention of the value generated by productive activity than the currently dominant but disarticulated and disruptive foreign corporate-led model.